2012
DOI: 10.1016/j.jbiotec.2012.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus haemolyticus prophage ΦSH2 endolysin relies on cysteine, histidine-dependent amidohydrolases/peptidases activity for lysis ‘from without’

Abstract: Staphylococcus aureus is an important pathogen, with methicillin-resistant (MRSA) and multi-drug resistant strains becoming increasingly prevalent in both human and veterinary clinics. S. aureus causing bovine mastitis yields high annual losses to the dairy industry. Conventional treatment of mastitis by broad range antibiotics is often not successful and may contribute to development of antibiotic resistance. Bacteriophage endolysins present a promising new source of antimicrobials. The endolysin of prophage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 69 publications
2
17
0
Order By: Relevance
“…One example is that of McCullers et al , 2007 [ 22 ], who used purified Cpl-1 lysin to effectively prevent acute otitis media in mice, inhibiting secondary bacterial infection following influenza infection, with no apparent toxicity of illness. Similar results for use of lysins as antimicrobials are reported in studies for other infections with potential applications against Staphylococci [ 23 , 24 ] and Streptococci [ 19 , 20 ].…”
Section: Discussionsupporting
confidence: 82%
“…One example is that of McCullers et al , 2007 [ 22 ], who used purified Cpl-1 lysin to effectively prevent acute otitis media in mice, inhibiting secondary bacterial infection following influenza infection, with no apparent toxicity of illness. Similar results for use of lysins as antimicrobials are reported in studies for other infections with potential applications against Staphylococci [ 23 , 24 ] and Streptococci [ 19 , 20 ].…”
Section: Discussionsupporting
confidence: 82%
“…This is not expected to be the case for HydH5 since the CHAP and LYZ2 domains, as single domains obtained via deletion analysis, have shown similar lytic activity on live cells [18], [19]. This similar activity of both domains contradicts the results previously reported by other authors since one of the two catalytic domains seems to be almost inactive in some modular endolysins [20][23]. Similarly, the lysostaphin endopeptidase domain is active in the triple-lytic domain fusion HydH5Lyso, as the specific activity of this construct on live cells is higher than that previously obtained for HydH5SH3b [19].…”
Section: Discussionmentioning
confidence: 62%
“…It was reported that optimum endolysin activity was achieved at a concentration of between 3 to 10 mM Ca 2+ . However, it must also be noted that they reported that the concentration of Mg 2+ had a negligible effect on enzyme activity, whilst the presence of Mn 2+ ions demonstrated an inhibitory effect, in vitro (Schmelcher et al, 2012). These data suggest that the chemical composition of food must be evaluated, as the activity of the endolysins, and hence the efficacy of the bacteriophages themselves could be adversely affected if not taken in to consideration.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Research by Schmelcher et al (2012) revealed that bacteriophage endolysin activity can be modulated by the concentration of divalent cations within the test medium. It was reported that optimum endolysin activity was achieved at a concentration of between 3 to 10 mM Ca 2+ .…”
Section: Accepted M Manuscriptmentioning
confidence: 99%